2022
DOI: 10.1111/febs.16672
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid‐bound FABP7 drives glioma cell proliferation through regulation of nuclear lipid droplet formation

Abstract: Fatty acid‐binding protein 7 (FABP7), one of the fatty acid (FA) chaperones involved in the modulation of intracellular FA metabolism, is highly expressed in glioblastoma, and its expression is associated with decreased patients' prognosis. Previously, we demonstrated that FABP7 requires its binding partner to exert its function and that a mutation in the FA‐binding site of FABP7 affects tumour biology. Here, we explored the role of FA ligand binding for FABP7 function in tumour proliferation and examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…6B). It should be noted that stressed cells caused by PUFA overload from the microenvironment activate protective membrane remodeling mechanisms to redistribute these PUFAs phospholipid membrane pools, and sequestered them into lipid droplets (LD) and TAGs pools, thereby preventing PUFA oxidation and cellular damage [56][57][58][59] . Moreover, it has been shown that the increase in LD formation in cells treated with FAs correlates with the number of double bonds in the FAs, and especially DHA-treated colorectal cancer cells (SiHa and HCT-116) showed the largest number of LDs formed 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6B). It should be noted that stressed cells caused by PUFA overload from the microenvironment activate protective membrane remodeling mechanisms to redistribute these PUFAs phospholipid membrane pools, and sequestered them into lipid droplets (LD) and TAGs pools, thereby preventing PUFA oxidation and cellular damage [56][57][58][59] . Moreover, it has been shown that the increase in LD formation in cells treated with FAs correlates with the number of double bonds in the FAs, and especially DHA-treated colorectal cancer cells (SiHa and HCT-116) showed the largest number of LDs formed 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in appropriate dishes and serum-deprived for 24 h prior to fatty acids (FAs) treatment. FAs were prepared in FA-free BSA-DPBS vehicle as described previously 59 . In brief, 1.2 mM FA stock was mixed with 3 mM FA-free BSA-DPBS vehicle and rotated for 1 h at 37 °C for conjugation.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…FABP7 has been identified as a protective factor for astrocytes against ROS toxicity by increasing intracellular LD accumulation, and significant upregulation of FABP7 in GBM cells promotes tumor cell proliferation and is linked to a bad prognosis. In addition to this, FABP4 interferes with macrophage-mediated verbal and behavioral responses and affects the release of proinflammatory molecules . The transmembrane glycoprotein CD36 promotes lipid sensing and transport to regulate lipid metabolism by facilitating endocytosis of FAs, among others. , Cancer cells respond to metabolic stress by activating or upregulating the ACSS2 expression to adapt to growth conditions within the TME and respond to metabolic stress .…”
Section: Metabolic Reprogramming In Gliomamentioning
confidence: 99%
“…In mammalian cells, nuclear LDs have been found to colocalize with promyelocytic leukemia (PML) bodies 16 , 21 , which are nuclear structures involved in the regulation of gene transcription 35 . In astrocytoma cells, fatty acid-binding protein 7 and oleic acids can accelerate the formation of nuclear LD–PML body complexes to upregulate the expression level of genes related to tumor proliferation 36 . Despite these important findings, the pathophysiological significance and frequency of nuclear LDs in hepatocytes in liver diseases remains unknown.…”
Section: Introductionmentioning
confidence: 99%